Segmentation of lymph nodes using CT images. - Yong, Tung Siong. (2010)
Lymph node size analysis is very important medically, especially in tumor staging. Node size may indicate tumor activity, and an even more important measure is the change of size over time. A method to calculate lymph node size involving diameter measurements and area calculations involve lymph node segmentation from a CT image. Conventional lymph node segmentation is time consuming, a pain-staking procedure and prone to human error. In our study, we have worked on the semi-automatic segmentation of lymph nodes using snakes active contour model coupled with an ideal image filter and an image edge detector.